Dr - Isaac K. Ofori (World Development, Elsevier, 2025)
This study advances the economic development scholarship through three key contributions. First, it examines the impact of distributional energy justice (hereafter referred to as energy justice) on inclusive human development (IHDI) in Africa. Second, we investigate how climate readiness moderates the effect of energy justice on IHDI. Third, we explore whether the joint effect of energy justice and climate readiness differs across low- and high-income African countries. We make these contributions using macro data for 36 African countries from 2010 to 2020. The results reveal that energy justice promotes IHDI. The contingency analysis also demonstrates that climate readiness amplifies the positive impact of energy justice on IHDI. Notably, across the economic, social, and governance perspectives of climate readiness, the results show that the moderating effect of governance readiness is striking. Evidence from sensitivity analysis also suggests that relative to their low-income counterparts, high-income countries realise a remarkable increase in IHDI with progress in energy justice and climate readiness. These findings underscore the urgent need for investments in energy justice and climate resilience to foster inclusive human development in Africa.
Keywords: Africa; Electricity access; Energy justice; Climate change readiness; Inclusive human development